ANALISIS ZAT PEMUTIH BERBAHAYA PADA KRIM MALAM DI KLINIK KECANTIKAN KOTA BANJARMASIN - Siska Musiam; Ratu Mouly Noor; Indah Fitri Ramadhani; Amaliyah Wahyuni; Riza Alfian; Eka Kumalasari; Saftia Aryzki (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
Face whitening cream is a facial lightening product that contains a mixture of chemicals and/or other ingredients with properties that can blot the black spots on the skin. Active ingredients that are often misused or added to excess in face whitening creams are mercury and hydroquinone. Whitening creams that contain mercury and hydroquinone are usually used in night creams related to the regeneration of skin cells that occur at night. The BPOM regulation states that the use of mercury is prohibited in cosmetics and the use of hydroquinone is still allowed for medical prescription purposes with a maximum limit of 4%. In this study testing of mercury and hydroquinone for night creams used in the beauty clinic of the city of Banjarmasin. Testing the presence of mercury using color reactions, and testing hydroquinone levels using spectrophotometry. The results showed that from 13 samples of night cream there were 3 positive samples containing mercury and hydroquinone simultaneously, 2 samples containing only mercury, 6 samples containing only hydroquinone, and 2 samples which did not contain mercury or hydroquinone. Of the 9 samples containing hydroquinone there were 5 samples that exceeded the maximum permissible level with the highest level was 11.41% (w/w).